Penerapan Algoritma Simplified Memory Bounded A* Pada Permainan Hangman Indonesia - Muhammad Yusuf Batubara; Mesran Mesran; Yasir Hasan (Universitas Budi Darma, 2021)
Learning Games are additional tools or facilities used to entertain and add insight to users. The use of learning games or education games is very suitable for children, teenagers and parents even at all ages. This educational game is very easy to reach and use because it is already in everyone's grasp, Hangman Game Mobile is a word game that aims to guess what the questioners mean by guessing the letters one by one so that they are arranged into a word. The Hangman game used to be only made from a piece of paper or on the blackboard in front of the students and asked the answer one by one to the students (students) so that with this activity there was a hangman game. Hangman game based on Android smartphone from several components that can be run inside the application such as letters, actors, hanging poles, ropes, answer columns. This research resulted in a Hangman game application aimed at Learning which was applied on an Android samartpone device and to be developed at a later date.